El significado del valor intrínseco en la ética ambiental - Gavilánez Elizalde, Franklin Gilberto (2024)
Expanding the boundaries of morality by reconceptualizing the intrinsic value of non-human nature is a promising philosophical option for the practice of a renewed and robust environmental ethics. Intrinsic value is a good in itself of all living entities in nature, which is why it is objective. This good has its etiology in some unique and unrepeatable evolutionary processes by natural selection. Intrinsic value is not derived from its utility, it is not a means, and it constitutes the purpose of all species of biodiversity in their different habitats, because that is their interest for the self-realization of their existence. Likewise, it is autonomous based on its usefulness or application based on another concept or subject. This kind of value in its definition is dependent on the human valuing consciousness, hence, it is subjective or anthropogenic. The general objective of this article is to characterize the intrinsic value in environmental ethics, for which a systematic review of current and relevant bibliographic material is carried out, around the categorization of the topic. The information has been subjected to processing, analysis and comparison to arrive at the reflections presented. The study determined that the structuring elements of Nature have intrinsic value in themselves, regardless of their usefulness or benefit that they could represent for human beings. Thus, these elements have an inherent value for their self-realization, which is their biological interest and, therefore, they must be respected and protected for the conservation of life.